Adat Mappasikarawa pada Perkawinan Masyarakat Bugis Perspektif Hukum Islam (Studi Kasus Desa Kaballangan Kabupaten Pinrang) - Syandri, Syandri; Bakry, Kasman; Salman Al Farisi (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2020)
This study aimed to determine the tradition Mappasikarawa in the marriage of the Bugis community from the perspective of Islamic law. The problems studied in this research are; First, how is the marriage tradition of the Bugis community, Second, what is the view of Islamic law on the Mappasikarawa tradition in Kaballangan Village, Duampanua District, Pinrang Regency, South Sulawesi. To find the answers to the above problems, the writer used the qualitative method (field research) by using normative, historical, and sociological approaches. The results of the research found are as follows: First, the Mappasikarawa tradition in the marriage of the Bugis Pinrang community is one of the activities performed before the marriage contract with the aim that the bride and groom get happiness, peace, prosperity, physically and spiritually in their life. Second, in the view of Islamic law, the Mappasikarawa tradition is not permissible in reference to a process that violates the rules of Islamic law in its implementation where the bride and the groom in direct contact before being a legal partner since Mappasikarawa is performed before the marriage contract. It means that there is an illegal interaction between two people who are not yet included in the mahram category